In the light of evolution - Avise, John C.; Ayala, Francisco Jose , 1934-; National Academy of Sciences (U.S.) (Washington, D.C. : National Academies Press, 2008)
Presents modern scientific perspectives on the evolutionary origin and maintenance of complex phenotypes including various behaviors, anatomies, and physiologies. This book includes 14 papers presented by distinguished evolutionists at the colloquium.
v. 1. Adaptation and complex design -- v. 2. Biodiversity and Extinction -- v. 3. Two Centuries of Darwin
Includes bibliographical references and index
Keywords: Evolution (Biology) -- Congresses